Compartmentalization of Free Fatty Acids in Blood-Feeding Tabanus bovinus Females - Mikołaj Drozdowski; Mieczysława Irena Boguś (Insects)
Lipids play vital roles in insect physiology, functioning as energy reserves, membrane constituents, and cuticular protectants. However, few studies have examined the anatomical distribution of lipids in blood-feeding Diptera and compared the compositions of the cuticular and internal compartments. This study analyzes the qualitative and quantitative profiles of free fatty acids (FFAs) in the female Tabanus bovinus, a hematophagous horsefly species, across different anatomical regions, including the head, wings, legs, thorax, and abdomen. The surface and internal lipid fractions were isolated using petroleum ether/dichloromethane extraction followed by sonication. GC-MS revealed the presence of 21 FFAs, including 16 saturated (C7:0, C8:0, C9:0, C10:0, C11:0, C12:0, C13:0, C14:0, C15:0, C16:0, C17:0, C18:0, C19:0, C20:0, C22:0, C24:0) and five unsaturated (C16:1, C18:2, C18:1, C20:5, C20:4). The head and wings showed the highest concentrations of cuticular FFAs. At the same time, internal lipid stores were most prominent in the thorax and abdomen (but four times lower than in the head cuticle), reflecting their role in energy storage and reproduction. All cuticular and internal extracts were dominated by C16:0, C18:0, and C18:1. Notably, several FFAs were undetected in specific compartments: C10:0 from inside the head, C11:0 and C13:0 from inside all examined body parts, C19:0 was absent from inside the head, wings and legs, while C20:5 and C20:4 were absent from both the cuticular and internal lipid pools of the wings. Interestingly, our analysis of the cuticle on the thorax and abdomen together revealed that both C13:0 and C19:0 were present only on the dorsal side, i.e., absent from the ventral side. These absences suggest a selective lipid metabolism tailored to the functional and ecological demands of T. bovinus females. Our findings suggest that the absence of specific compounds from individual body parts may serve as an indicator of physiological specialization. This work provides new insights into lipid compartmentalization in Tabanidae and offers a framework for future comparative and ecological lipidomics studies in insects.